2010
DOI: 10.1017/s0144686x10000309
|View full text |Cite
|
Sign up to set email alerts
|

Views of life and sense of identity in people with Alzheimer's disease

Abstract: Making it possible for people with Alzheimer's disease to retain a sense of identity during the process of the disease poses a great challenge to care-givers, professionals and family carers. The aim of this study is to elucidate the role of the view of life of people with Alzheimer's in framing their sense of identity. Is their view of life a vital aspect of their sense of identity? ' View of life ' was interpreted as a vital aspect of sense of identity, understood as the individual's beliefs about their life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 54 publications
0
23
0
2
Order By: Relevance
“…Still, the essence of the experience of dementia is that the development of self is eroded (Caddell & Clare, 2010; Mograbi, Brown, & Morris, 2009; Westius, Kallenberg, & Norberg, 2010). The self can no longer be maintained and linked to memory and recollection of the past, of the autobiography; and the cognitive ability to connect events, places and people becomes lost (Jetten, Haslam, Pugliese, Tonks, & Haslam, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Still, the essence of the experience of dementia is that the development of self is eroded (Caddell & Clare, 2010; Mograbi, Brown, & Morris, 2009; Westius, Kallenberg, & Norberg, 2010). The self can no longer be maintained and linked to memory and recollection of the past, of the autobiography; and the cognitive ability to connect events, places and people becomes lost (Jetten, Haslam, Pugliese, Tonks, & Haslam, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Certain participants stated that life must take its course and that one must accept what occurs and live in the moment. Westius et al (2010) found that by narrating their life story, people with mild and moderate AD also narrated their understanding of reality, their system of values, and their basic emotional attitudes. This interpretation is consistent with a report that people with AD sought to act in accordance with their values (McFadden, Ingram, & Baldauf, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Even for older adults with restricted cognitive-linguistic abilities, conversation based on reminiscence acknowledges, affirms, and values life experiences as topics of discussion, adding to meaningful social roles and improving health-related quality of life (Hilari & Northcott, 2006). Telling stories about one's life provides a sense of identity, meaningfulness, and continuity, even for those with cognitive or linguistic challenges (Westius, Kallenberg, & Norberg, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Rich conversation is possible when one partner has a significant language impairment, often through multimodal communication (Goodwin, 2003). Topics that are woven into social relationships and give each person a unique personality are the first ones lost with challenges to spontaneous language and the subsequent verbal isolation and reduced sense of self-identity (Westius et al, 2010).…”
Section: Discussionmentioning
confidence: 99%